1995
DOI: 10.1073/pnas.92.3.669
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-based selection for bacterial genes that are specifically induced during infection of a host.

Abstract: We have recently described a genetic system, termed in vivo expression technology (IVET), that uses an animal as a selective medium to identify genes that pathogenic bacteria specifically express when infecting host tissues. Here, the potential utility of the IVET approach has been expanded with the development of a transcriptional-fusion vector, pIVET8, which uses antibiotic resistance as the basis for selection in host tissues. pIVET8 contains promoterless chloramphenicol acetyltransferase (cat) and lacZY ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
159
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(160 citation statements)
references
References 26 publications
1
159
0
Order By: Relevance
“…B. Finlay, unpublished results), a utilizable sugar for Salmonella. A previous report, supporting our findings, has suggested that fad genes are specifically expressed during Salmonella pathogenesis (Mahan et al, 1995). It is clear, however, from these various studies that stationary phase, C-starvation and …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…B. Finlay, unpublished results), a utilizable sugar for Salmonella. A previous report, supporting our findings, has suggested that fad genes are specifically expressed during Salmonella pathogenesis (Mahan et al, 1995). It is clear, however, from these various studies that stationary phase, C-starvation and …”
Section: Discussionsupporting
confidence: 80%
“…This knowledge may provide insight into the conditions present in an intracellular environment as well as clues as to the potential importance of a locus in pathogenesis (Mahan et al, 1995;Valdivia & Falkow, 1997). T o this end, strains ST54 and ST64 were incubated in the presence of MDCK epithelial cells in tissue culture, and allowed to be internalized within these cells.…”
Section: The Fadf Gene Is Induced Within Cultured Mdck Epithelial Celmentioning
confidence: 99%
“…during iron restriction or during experimental infection. This system differs from the antibiotic-based IVET system described for Salmonella typhimurium (Mahan et al, 1995) in two ways. One is that the lacZ reporter gene fusion is omitted in our vector constructions because inclusion of the lacZ gene resulted in structural instability of the vector.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several approaches have been reported that allow the identification of genes that are specifically expressed in the host. Examples are signature-tagged mutagenesis (STM) and in vivo expression technology (IVET ; Mahan et al, 1993Mahan et al, , 1995Camilli & Mekalanos, 1995 ;Hensel et al, 1995 ;Mei et al, 1997 ;Young & Miller, 1997 ;Chiang & Mekalanos, 1998 ;Coulter et al, 1998 ;Lowe et al, 1998 ;Polissi et al, 1998 ;Camacho et al, 1999 ;Darwin & Miller, 1999 ;Edelstein et al, 1999 ;Fuller et al, 1999 ;Zhao et al, 1999). In addition, important virulence proteins could also be identified by the selection of genes specifically expressed under conditions mimicking in vivo conditions, for example by growth under ironrestricted conditions (Litwin & Calderwood, 1993 ;Martinez et al, 1990).…”
Section: Abbreviation : Ivet In Vivo Expression Technologymentioning
confidence: 99%
“…A strategy which allows the detection of salmonella genes that are specifically induced in host tissues has been developed by Mahan and colleagues [236]. The strategy, named in i o expression technology (IVET), takes advantage of the fact that purine auxotrophy greatly attenuates growth of Typhimurium in the animal host ; this deficiency provides a strong selection for a PurA + phenotype in animal tissues.…”
Section: Recently Developed Molecular Methods With Application To Stumentioning
confidence: 99%